Specific training effects of concurrent aerobic and strength exercises depend on recovery duration - Robineau, J.; Babault, N.; Piscione, J.; Lacome, M.; Bigard, A. X. (The Journal of Strength and Conditioning Research, 2016)
This study aimed to determine whether the duration (0, 6, or 24 hours) of recovery between strength and aerobic sequences influences the responses to a concurrent training program. Fifty-eight amateur rugby players were randomly assigned to control (CONT), concurrent training (C-0h, C-6h, or C-24h), or strength training (STR) groups during a 7-week training period. Two sessions of each quality were proposed each week with strength always performed before aerobic training. Neuromuscular and aerobic measurements were performed before and immediately after the overall training period. Data were assessed for practical significance using magnitude-based inference. Gains in maximal strength for bench press and half squat were lower in C-0h compared with that in C-6h, C-24h, and STR. The maximal voluntary contraction (MVC) during isokinetic knee extension at 60°/s was likely higher for C-24h compared with C-0h. Changes in MVC at 180°/s was likely higher in C-24h and STR than in C-0h and C-6h. Training-induced gains in isometric MVC for C-0h, C-6h, C-24h, and STR were unclear. VO2peak increased in C-0h, C-6h, and C-24h. Training-induced changes in VO2peak were higher in C-24h than in C-0h and C-6h. Our study emphasized that the interference on strength development depends on the recovery delay between the 2 sequences. Daily training without a recovery period between sessions (C-0h) and, to a lesser extent, training twice a day (C-6h), is not optimal for neuromuscular and aerobic improvements. Fitness coaches should avoid scheduling 2 contradictory qualities, with less than 6-hour recovery between them to obtain full adaptive responses to concurrent training.